Pengaruh Stres Kerja dan Self Esteem terhadap Kinerja Karyawan dengan Quality of Worklife sebagai Mediasi - Roy Suryaningrat; Hardani Widhiastuti (Pusat Riset dan Inovasi Nasional, 2026)
This study is motivated by the decline in employee performance at BCA KCU Tegal and the instability in achieving targets, indicating the influence of internal factors such as work stress, self-esteem, and quality of work life. This study aims to analyze the effect of work stress and self-esteem on quality of work life (QWL), their influence on employee performance, as well as the role of QWL as a mediator. The method employed is a quantitative explanatory approach, involving all 53 employees through a census technique and analyzed using Partial Least Square (PLS). The results indicate that work stress and self-esteem significantly affect performance, while QWL only serves as a predictor without mediating the relationships among variables. These findings confirm that the dynamics of work pressure and employees’ psychological factors are more dominant in shaping performance compared to perceptions of the work environment. The study’s implications highlight the importance of stress management strategies, strengthening self-esteem, and improving working conditions to promote optimal performance, while also opening opportunities for further research with broader scope and more comprehensive methods.